Measuring Muslim Welfare: A Falah-Based Index - Muhammad Arfan Harahap; Sukiman Sukiman; Isnaini Harahap (Faculty of Islamic Economics and Business, Universitas Islam Negeri Ar-Raniry, 2023)
The concept of welfare remains a subject of ongoing debate, and the prevailing frameworks for assessing welfare need to be adapted to align with Islamic principles. This study delves into the concept of falah, a state of well-being rooted in Islamic values, to develop a 'falah welfare index' and analyze it within a Muslim community in Langkat Regency, Indonesia. Additionally, the study explores the variables that influence falah welfare. Employing a mixed-methods approach with an exploratory sequential design, this research qualitatively constructs a falah welfare index and quantitatively measures both community welfare levels and the impact of predictor variables on the criterion variable of falah welfare. A key finding of this study is the establishment of a falah welfare index comprising three categories: fakir (extreme poverty), miskin (poor), and falah (well-being). Moreover, the results reveal a positive influence of religiosity, Islamic work ethics, Islamic consumption ethics, Islamic investment patterns, and Islamic wealth management on falah welfare. The implications of this research offer a novel approach to measuring welfare within Muslim societies and solidify the concept of falah as a cornerstone of welfare evaluation from an Islamic economic perspective.==============================================================================================================ABSTRAK – Pengukuran Kesejahteraan Muslim: Analisis Indeks Berbasis Falah. Kesejahteraan masih menjadi fenomena yang terus diperdebatkan dan pengukuran kesejahteraan seorang Muslim perlu disesuaikan dengan karakteristik ke-Islaman. Tujuan penelitian ini untuk mengeksplorasi konsep falah dalam membangun ‘Indeks Kesejahteraan Falah’ dan menganalisis tingkat kesejahteraan masyarakat Muslim di Kabupaten Langkat, Sumatera Utara, Indonesia. Selain itu, penelitian ini juga menganalisis variabel yang mempengaruhi variabel kesejahteraan falah. Penelitian ini menggunakan metode campuran (mixed method) dengan desain exploratory sequential. Indeks kesejahteraan falah diinisiasi dengan metode kualitatif sementara metode kuantitatif digunakan untuk pengukuran terhadap tingkat kesejahteraan masyarakat dan pengujian pengaruh dari masing-masing variabel predictor terhadap variabel criterion. Analisis data dilakukan dengan pendekatan Structural Equation Modeling-Partial Least Square (SEM-PLS). Temuan utama penelitian ini adalah terbangunnya indeks kesejahteraan falah dengan tiga kategori tingkatan yaitu fakir, miskin dan falah. Kajian ini juga menunjukkan adanya pengaruh positif variabel religiositas, etika bekerja Islami, etika konsumsi Islami, pola investasi Islami dan pengelolaan harta Islami terhadap variabel Kesejahteraan Falah. Hasil ini berimplikasi dalam memberikan alternatif baru dalam pengukuran tingkat kesejahteraan masyarakat Muslim dan membuktikan soliditas konsep falah sebagai metode pengukur kesejahteraan dalam perspektif ekonomi Islam.